2011
DOI: 10.1177/0363546511420810
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of Knee Joint Laxities and Graft Forces After Anterior Cruciate Ligament Reconstruction by Anteromedial Portal, Outside-In, and Transtibial Techniques

Abstract: Background Recently, anatomic anterior cruciate ligament (ACL) reconstruction is emphasized to improve joint laxity and to potentially avert initiation of cartilage degeneration. There is a paucity of information on the efficacy of ACL reconstructions by currently practiced tunnel creation techniques in restoring normal joint laxity. Study Design Controlled laboratory study. Hypothesis Anterior cruciate ligament reconstruction by the anteromedial (AM) portal technique, outside-in (OI) technique, and modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 20 publications
4
45
0
1
Order By: Relevance
“…These results are consistent with Schairer et al [38] and Sim et al [40] who found no difference in AP translation compared with the intact knee with either the TT or AM technique. This is in contrast to Bedi et al [9,10] who found the AM technique to result in more accurate positioning of the ACL footprint compared with the TT technique, which corresponded with less tibial translation according to the Lachman and pivot shift test as tested on five matched cadaveric knee pairs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are consistent with Schairer et al [38] and Sim et al [40] who found no difference in AP translation compared with the intact knee with either the TT or AM technique. This is in contrast to Bedi et al [9,10] who found the AM technique to result in more accurate positioning of the ACL footprint compared with the TT technique, which corresponded with less tibial translation according to the Lachman and pivot shift test as tested on five matched cadaveric knee pairs.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, Sim et al found that when torque was applied, the modified TT technique, which placed the tibial tunnel in the posterolateral quadrant of the intact footprint, failed to restore intact anterior tibial translation at both 0°and 30°c ompared with the AM technique, which only failed to do so at 30°. However, similar to our study, Sim et al [40] went on to conclude that both techniques were similar in their ability to restore rotational stability of the knee. The similar results in our patient cohorts could be attributed to the fact that the surgeons erred for a more anatomic position, especially for the femoral socket.…”
Section: Discussionsupporting
confidence: 88%
“…Much of this work has evaluated and improved the efficaciousness of surgical methods and graft material selections used in ACL reconstructions with respect to native ACL biomechanics [12,15,19,20,28,35,43,49,51,[56][57][58]. These simulations have also gathered data on the mechanical contributions of the intact ACL in response to Lachman's and pivot shift tests [15,19,20,28,35,43,49,51,[56][57][58], gait cycles [23,39], and landing impact forces [32,40,41,46,52,53]. The accrued data have advanced the knowledge of ACL function and provided a baseline of comparison by which to evaluate the effectiveness of ACL injury treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Anatomic anterior cruciate ligament (ACL) reconstruction is emphasized to improve joint laxity and to potentially avert initiation of cartilage degeneration. There is a paucity of information on the efficacy of ACL reconstructions by currently practiced tunnel creation techniques in restoring normal joint laxity (2).…”
Section: Discussionmentioning
confidence: 99%
“…Anatomic ACL reconstruction improves joint laxity and prevents degeneration of cartilage (2). In ACL reconstruction nowadays, the importance is and should rightly be given to anatomical graft placements to recreate normal physiologic graft tension and more knee kinematics (3).…”
Section: Introductionmentioning
confidence: 99%